ORGANIZATION OF BACKGROUND KNOWLEDGE STRUCTURES IN LEGAL LANGUAGE AND RELATED TRANSLATION PROBLEMS - BIEL, Łucja (Comparative Legilinguistics, 2009)
The paper examines the organization of background knowledge structures in legal language and related incongruities of legal terms. The cognitive linguistics methodology, in particular its findings on the nature of meaning, is applied. Terms serve as prompts with a semantic potential to activate various levels of knowledge structures, such as domains, scripts, scenarios, cognitive models and frames. In most cases organization of knowledge will differ in the SL and TL. The final part analyses translation strategies and techniques in terms of their potential to activate relevant knowledge.